Revealing the impact of loss: Exploring mental health through the use of drawing/writing with HIV positive adolescents in Johannesburg - Woollett, N; Brahmbhatt, H; Dodd, K; Booth, M; Berman, H; Cluver, L (Elsevier, 2017)
Due to dramatic improvements in access to antiretroviral treatment (ART), children born with perinatal HIV infection are growing into adolescence in large numbers, especially in low and middle income countries (LMICs). Approximately 2.1 million adolescents in LMICs were living with HIV in 2012, and of the nearly 3.2 million children under the age of 15 years infected with HIV globally, 90% are living in sub-Saharan Africa. The HIV pandemic has increasingly brought attention to the unmet mental health needs of children and adolescents, highlighting the comorbidity of HIV and mental health problems especially among those perinatally infected . These children and adolescents tend to experience enduring adversity. Multiple losses and bereavement, numerous sicknesses and hospitalisations, poor school attendance, increased poverty and exposure to violence, stigma and discrimination, disclosure challenges, as well as low levels of physical and psychosocial support furthers their risk for developing mental health problems